Performance investigation and emission analysis of a diesel engine operated on hydrogen and ammonia - Kanberoglu, Berna; Okumus, Fatih; Sonmez, Halil Ibrahim; Gonca, Guven; Kokkulunk, Gorkem; Kaya, Cenk; Aydin, Zafer (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study investigates binary-fuel operation of a single-cylinder diesel engine using hydrogen and ammonia as secondary fuels through comprehensive CFD simulations. The effects of injector hole diameter, injection timing, and injection duration on combustion, performance, and emissions were systematically analyzed under both full-and partial-load conditions. Parametric analyses further revealed that variations in nozzle diameter and injection duration exerted a stronger influence on indicated power and efficiency than intake air conditions. The results indicate that injector geometry strongly influences combustion dynamics. At full load, indicated power averaged 6.0 kW, with the highest value of 6.5 kW obtained in ammonia-diesel operation at the smallest nozzle diameter. At partial load, hydrogen demonstrated superior stability, achieving the highest thermal efficiency of 43.17 % in the L50D100 configuration. A 0.05 mm increase in injector hole diameter reduced NO emissions in hydrogen-diesel operation by 24.7 %, highlighting the sensitivity of NO formation to injector design. Fuel type largely dictated emission characteristics. Hydrogen consistently produced very low CO2 emissions (approximately 459 g/kWh) owing to its carbon-free nature, though it tended to elevate NO levels due to high combustion temperatures. Ammonia, by contrast, provided lower NO and CO2 emissions under partial load but showed reduced indicated power and efficiency compared to hydrogen. Intake air conditions also played a significant role: increasing intake pressure by 0.2 bar lowered CO2 emissions by up to 27 g/kWh in the L50D100 configuration. Overall, the study demonstrates that binary-fuel diesel operation with hydrogen and ammonia is highly sensitive to engine operating parameters.
Keywords: Alternative fuels; Ammonia; Hydrogen; Decarbonization; Engine performance; Diesel engine; INTAKE AIR-TEMPERATURE; COMPRESSION IGNITION ENGINE; ENERGY SHARE; COMBUSTION; FUEL; PRESSURE; PROGRESS; Thermodynamics; Energy & Fuels; Engineering; Mechanics